Modeling Discontinuous Cultural Evolution: The Impact of Cross-Domain Transfer - Ganesh, Kirthana; Gabora, Liane (Frontiers in Psychology, 2022)
This paper builds on an earlier model that used autocatalytic networks to model the cognitive mechanisms underlying the transition to behavioral-cognitive modernity in the Upper Paleolithic, using as an example, the oldest-known uncontested example of figurative art: the carving of the Hohlenstein-Stadel Löwenmensch, or lion-human. Autocatalytic networks provide a general modeling setting in which nodes are not just passive transmitters of activation; they actively galvanize, or ‘catalyze’ the synthesis of novel (‘foodset-derived’) nodes from existing ones (the ‘foodset’). This makes them uniquely suited to model how new structure grows out of earlier structure, i.e., cumulative, generative network growth. They have been used to model the origin and early evolution of biological life, and the emergence of cognitive structures capable of undergoing cultural evolution. Here they are used to model discontinuous cultural transitions involving cross-domain transfer. We conducted a study in which six individual creators and one group generated music, prose, poetry, and visual art inspired by the Hohlenstein-Stadel Löwenmensch, and answered questions about the process. The data revealed four through-lines by which they expressed the Löwenmensch in an alternative art form: (1) lion-human hybrid, (2) subtracting from the whole to reveal the form within, (3) deterioration, (4) waiting to be found with a story to tell. Autocatalytic networks were used to model how these four spontaneously derived through-lines form the backbone of a cultural lineage from Löwenmensch to artist to audience. We used the resulting data from three creators to model the cross-domain transfer from inspirational source (sculpted figurine) to creative product (music, poetry, prose, visual art). These four spontaneously-generated threads of cultural continuity formed the backbone of this Löwenmensch-inspired cultural lineage, enabling culture to evolve even in the face of discontinuity at the level conventional categories or domains. We know of no other theory of cultural evolution that accommodates cross-domain transfer or other forms of discontinuity. The approach paves the way for a broad scientific framework for the origins of evolutionary processes.